A graph signal processing‐based multiple model Kalman filter (GSP‐MMKF) tool for predictive analytics: An air separation unit process application. Issue 4 (9th May 2022) - Ghosh, Sambit; Yerimah, Lucky E.; Wang, Yajun; Cao, Yanan; Flores‐Cerrillo, Jesus; Bequette, B. Wayne
Abstract: The industrial Air Separations Unit (ASU) is a complicated and tightly operated process. The use of dynamic process analytics is also a key element of safe and economic operation of these processes, with increasing focus on predictive analytics to take preemptive actions. With the availability of real‐time data from hundreds of sensors, the data analysis process should also consider the topology of the data, as seen in sensor networks. In this paper, a novel tool is presented that considers the complex connectivity patterns in the sensor network and uses local adaptive disturbance estimations to predict global network‐scale trends. The paper introduces the emerging field of Graph Signal Processing (GSP) and presents a rigorous derivation of the tool starting from the extraction of the sensor‐network (in a graph theoretical sense) from the data. This network, which is in the form of a matrix, is then used to derive a Kalman‐filter type of state‐space model driven by input disturbances. Multiple disturbance models (e.g., step, ramp, periodic) are included to allow the model to have different kinds of disturbance propagation. Each graph node (representing the sensors used) dynamically adapts to the most recent detected disturbance individually. These estimated disturbances are propagated to the global network using the graph. Modifications to ensure stability are also discussed. The fidelity of the tool is tested on certain downtime events and the paper concludes by discussing the advantages of the method and planned future improvements. Abstract : The paper presents a novel predictive analysis tool that combines Graph Signal Processing and Multiple Model Kalman Filters (GSP‐MMKF). An application on a cryogenic Air Separation Unit plant data is demonstrated.